A High-Resolution Liquid Chromatography-Mass Spectrometry Method for Identification of Toxic Natural Products in Clinical Cases. (28th October 2020) - Luo, Y R; Yun, C; Lynch, K L; Comstock, K
Abstract: Introduction/Objective: Many natural products have biological effects on humans and animals. Poisoning caused by natural products is often found in clinical toxicology cases. Liquid chromatography-high-resolution-mass spectrometry (LC-HRMS) has recently emerged as a powerful analytical tool for large-scale target screening, and the application of LC-HRMS can be expanded to solve the clinical cases of natural product poisoning. Methods: The LC-HRMS method is based on a spectral library of 121 natural products. The spectral library was constructed by analyzing standards either in a Q-TOF mass spectrometer (only MS 2 spectra acquired) or in an Orbitrap Tribrid mass spectrometer (MS 2 and MS 3 spectra acquired). Results: The LC-HRMS method was verified for the limit of detection (LOD) and matrix effects in both serum and urine matrices. For each compound, the LOD was evaluated from 1.0 ng/ml to 1000 ng/ml for urine samples and from 0.50 ng/ml to 500 ng/ml for serum samples. The matrix effects were determined at three concentration levels andranged from 30.4% to 123.5% for urine samples and from 23.4% to 132.9% for serum samples. The LC-HRMS method was successfully applied to identify the culprits in three clinical cases. In addition, the combined use of MS 2 and MS 3 spectra enhanced the accuracy of compound identification, in library search reducing the importance of retention time that varies among instruments and consumable lots. In Case 1, the patient presented with paresthesias, arrhythmias, and stiffened arms and legs. The toxic alkaloid aconitine was identified in the serum sample and the extract of herbs that the patient ingested. In Case 2, the patients presented with weakness, dizziness, and vomiting. The symptoms were caused by mistakenly taking Nicotiana glauca leaves and the alkaloid anabasine was identified as the culprit. In Case 3, the patients were suspected of intoxicated by taking too much extract of lupini beans. The culprit alkaloids from lupini beans lupanine and sparteine were found in the serum samples. Conclusion: The involvement of a toxicology laboratory with the capability to perform the LC-HRMS method and with experience in the investigation of undifferentiated cases provides a unique diagnostic advantage in cases where exposure to toxic substances is possible.